بناء اختبار محكي المرجع في مناهج البحث العلمي للدراسات العليا والتحقق من دلالات فاعلية الاختبار وفقراته وفق النظريتين الكلاسيكية والحديثة في القياس - الخالدي، هاني سليمان أحمد (جامعة المنصورة - كلية الاداب, 2015)
هدفت الدراسة الحالية إلى بناء اختبار محكي المرجع في مناهج البحث العلمي للدراسات العليا والتحقق من دلالات الفاعلية للاختبار وفقراته وفق النظريتين الكلاسيكية والحديثة في القياس (وفقا للنموذج اللوجستي ثنائي المعلم)، ولتحقيق هذا الهدف تم بناء اختبار في مادة مناهج البحث، يقيس تحصيل الطالب في مادة المناهج، تألف الاختبار من (٤٠) فقرة من نوع الاختيار من أربعة بدائل، تكونت عينة الدراسة من (٢٥٣) طالب من طلبة الدراسات العليا في جامعة نايف العربية للعلوم الأمنية. أظهرت نتائج الدراسة ما يأتي: بالنسبة للنظرية الكلاسيكية فقد تم حذف فقرتين فقط كان تمييزهما منخفض ليصبح الاختبار مكونا من (٣٨) فقرة، وكان المتوسط العام لصعوبة الفقرات يساوي (0.79)، ومتوسط تمييز الفقرات يساوي (0.41). أما فيما يتعلق بالنظرية الحديثة في القياس فقد تم التحقق من افتراضاتها. وأظهرت النتائج عدم مطابقة (١٣) فقرة للنموذج اللوجستي ثنائي المعلم، حيث كانت قيمة احتمالية المطابقة لكل منها أقل من (0.01)، لذلك تم حذف هذه الفقرات غير المطابقة للنموذج، وعليه تم الحصول على اختبار محكي المرجع في مادة مناهج البحث العلمي والذي تكون في صورته النهائية من (٢٧) فقرة، حيث تراوحت قيم الصعوبة بين (0.238) و (3.172) وبمتوسط حسابي قدره (1.649)، وقيم التمييز تراوحت بين (0.75) و(5.336) وبمتوسط حسابي قدره (2.11).
Building a Criterion Test for Research Curriculums in Post Graduate Studies and Investigating its Effectiveness and items according to Classical and Modern Theories of Measurement This study aimed to create a criterion test for in academic research curriculums in post graduate studies, and to investigate its effectiveness and items according to classical and modern theories of measurement (according to the binary logistic model parameter). To achieve this goal, a test was created for a research methodologies study unit to measure the extent of learning by students in this subject. The subject was made up from 40 items; of a kind choose from four alternatives. The study sample was made up from 253 students in postgraduate study programs in Naif Arab University for Security Sciences. Results of the study revealed the following: According to the classical theory only 2 item were removed. Their differential was low which resulted in the test being only 38 item. The general average for the difficulty of the items was equal to (0.79) and the average differential items was equal to (0.41). As for the modern theory of measurement, its hypotheses were conformed. Results revealed a lack of conformity in 13 item of the binary logistic model parameter. The potential value of conformity between them was less than (0.01). Therefore, these items, which were not in conformity with the model, were removed. Based on this, a criterion test was created in the academic research subject, which was made up at the end of the study from 27 item. The difficulty values ranged between (0.238) and (3.172) and a calculated average of (1.649), the differential values ranged between (0.75) and (5.336) and a calculated average of (2.11).
Keywords: البحث العلمي -- الاختبارات مرجعية المحك -- الاختبارات الإحصائية -- علم النفس -- المقاييس النفسية